Pengaruh Kepemimpinan Kepala Sekolah, Lingkungan Sekolah, dan Disiplin Terhadap Prestasi Siswa SMA Muhammadiyah 8 Sukodadi Lamongan - Annas Zusriyansyah; Mochammad Agung Surianto (Jurnal Mahasiswa Manajemen, 2022)
Background - The quality of the principal's leadership, the school environment and discipline at school do not affect student achievement, because basically an educational institution is expected to provide good teaching services and produce outstanding students. This is evidenced by the influence of achievement at SMA Muhammadiyah 8 Sukodadi, Lamongan. Objective - The purpose of this study was to determine the influence of the principal's leadership, school environment, and discipline on student achievement at SMA Muhammadiyah 8 Sukodadi, Lamongan. Design/Methodology/Approach - This research is quantitative research with a descriptive approach, the instruments used in this study used a questionnaire with the variables of Principal Leadership, School Environment, and Discipline on Student Achievement with the aim of obtaining information from respondents. Findings - The results of this study indicate that there is an influence of the principal's leadership on student achievement with a significance value of 0.000 <0.05, and there is an influence of the school environment on student achievement with a significance value of 0.002 <0.05 and there is an influence of discipline on student achievement with a significance value of 0.029 with a coefficient 70% determination. Research implications - This research contributes to leadership, environment and discipline in schools in order to maintain the quality of student achievement at SMA Muhammadiyah 8 Sukodadi, Lamongan. Research limitations - This research is only conducted on employees who carry out dual roles at PT Mustika Karya Anugrah Surabaya. This research was only conducted on students of SMA Muhammadiyah 8 Sukodadi, Lamongan.